Let be a continuous function such that:
If , enter as your answer.
Notation: denotes the floor function .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We can move the LHS integral to the RHS to get:
∫ 2 1 5 0 ( f 2 ( x ) − ( x − 1 ) l n ( x − 1 ) ( 2 f ( x ) − ( x − 1 ) l n ( x − 1 ) ) ) d x = 0 ⇒
∫ 2 1 5 0 ( f 2 ( x ) − 2 f ( x ) ( x − 1 ) l n ( x − 1 ) + ( ( x − 1 ) l n ( x − 1 ) ) 2 ) d x = 0 ⇒
∫ 2 1 5 0 ( f ( x ) − ( x − 1 ) l n ( x − 1 ) ) 2 d x = 0
But, ( f ( x ) − ( x − 1 ) l n ( x − 1 ) ) 2 ≥ 0 , so:
( f ( x ) − ( x − 1 ) l n ( x − 1 ) ) 2 = 0 ⇒
f ( x ) − ( x − 1 ) l n ( x − 1 ) = 0 ⇒
f ( x ) = ( x − 1 ) l n ( x − 1 )
Therefor:
f ( 1 0 1 ) = 1 0 0 × l n ( 1 0 0 ) ⇒
A ≈ 4 6 0 . 5 1 7 ⇒
⌊ A ⌋ = 4 6 0